Serum electrolytes in senile cataract patients - Usha S. Adiga; Adline Harris; T.N. Ezhilvathani; Sharbari Basu (Al Ameen Medical College, 2014)
Introduction: Cataract refers to opacification of crystalline lens in the human eye. Globally, cataract accounts for 50% of blindness and remains the leading cause of visual impairment all over the world, despite improvements in surgical outcomes. Age is the strongest known non-modifiable risk factor for cataract formation. One of the proposed risk factors for cataract formation is rise in serum sodium ion level. Role of potassium and chloride are inconclusive Even though ageing cannot be prevented, physiological changes that occur in electrolytes can be modified. The aim of the study was to estimate serum electrolyte levels in senile cataract patients as compared to those without cataract. Methods: This study includes hundred senile cataract patients and age matched hundred healthy people without cataract. Serum electrolytes were estimated by using an electrolyte analyzer which works on the principle of ion selective electrodes. Results: We noted a highly significant (p<0.0001) rise in sodium levels in cases (146.35 ± 3.49 meq/l) as compared to controls (142.77 ± 3.75meq/l).Chloride levels were also significantly elevated (p<0.05) in cases (102.32 ± 4.10meq/l) as compared to controls (100.82 ± 4.12 meq/l). Serum potassium level, even though elevated in cases, it was statistically insignificant. Conclusion: From this study we can conclude that sodium and chloride may be used as markers of senile cataract formation. Dietary salt restriction may help to lower the sodium and chloride levels and delay the process of cataract formation.